Retelling Fragmented Histories: Partition in Short Stories (Prithvi Academic Journal, 2023)
Partition of India in 1947 has been one of the major events in the history of South Asia that has played a crucial role in shaping the three nations of India, Pakistan and Bangladesh. A number of narratives on the background of partition have given rise to the sub-genre of partition narratives in which the authors reflect and reconstruct the pain, suffering, loss and alternative histories of the events of partition. The authors, in their effort, give a voice to the victims and critique the political players. Partition in the Bengal and Assam border is represented in a number of writings. In this article, an attempt is made to give a glimpse of the partition narratives written in Bangla through three short stories from Debes Ray’s Raktamanir Haare [In the Garland of Blood Beads] published by Sahitya Akademy. The stories are the poignant snapshots of the events of partition in the Bengal border. The stories show the life of suffering of people caused by partition and also upheld the resilient spirit of life.